2001
DOI: 10.1002/rcm.280
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase attachment of water and methanol to Ag(I) complexes with α‐amino acids in an ion trap mass spectrometer

Abstract: Electrospray ionization was used to generate gas phase complexes of Ag+ with selected alpha-amino acids. Following storage (isolation without collisional activation) in an ion trap mass spectrometer, the mass spectra produced from the complexes of Ag+ with alpha-amino acids such as alanine, valine and tert-leucine contained peaks consistent with the formation of water or methanol molecule adduct ions. The same adduct ions were not present, however, in the mass spectra generated from the Ag+ complexes with phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 31 publications
5
56
0
Order By: Relevance
“…These adducts are most likely produced in the front-end of the mass spectrometer as previously described. These observations corroborate the formation of methanol and water adduct species to fragment ions of the Ag ϩ -phenylalanine complex most recently reported [41,46]. The structure at the global minimum on the Ag ϩ -phenylalanine complex surface is shown below (Structure 1, see also Scheme 2).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These adducts are most likely produced in the front-end of the mass spectrometer as previously described. These observations corroborate the formation of methanol and water adduct species to fragment ions of the Ag ϩ -phenylalanine complex most recently reported [41,46]. The structure at the global minimum on the Ag ϩ -phenylalanine complex surface is shown below (Structure 1, see also Scheme 2).…”
Section: Resultssupporting
confidence: 87%
“…The stability of this ion is attributed to Ag ϩ -interaction with the phenyl ring. After the submission of this contribution, a paper by Perera et al [46] appeared in which most of the observations and conclusions independently reported here are corroborated. We thank one of the reviewers for pointing out possible alternative pathways for the fragmentation reactions observed for the Ag ϩ -phenylalanine complex that involve activation of and insertion of the metal ion into various C™C, C™N, and C™H bonds and eventual fragmentation, which have previously been suggested for Cu ϩ -phenylalanine [40,47] and for Ag ϩ -hydrocarbon complexes [45].…”
Section: Resultssupporting
confidence: 62%
“…Likely, the attached water molecule is dislodged during collisional activation, but then rapidly reattaches before ion detection. This type of solvent adduction process has been commonly observed for transition-metal complexes in a quadrupole ion trap [23][24][25][26][27]. This was the same fragmentation pattern observed for the dissociation of the watersolvated 1:1 complexes containing 6, 7, and 8 and a transition-metal.…”
Section: Ligand Binding To Metalssupporting
confidence: 76%
“…During the isolation step, all ionized species except the one chosen for storage are resonantly ejected from the ion trap. The appearance of peaks 18 u higher than the isolated ion is indicative of the formation of H 2 O adducts [23][24][25]; the abundance of the adducts increased as the isolation and storage time was extended. The formation of abundant H 2 O adducts indicates that several of the uranyl complex ions show a significant tendency to accept ligands via gas-phase association reactions in the ion trap.…”
Section: Resultsmentioning
confidence: 99%
“…To gain a better understanding of the intrinsic interactions between different uranyl species and solvent, we have begun an investigation of uranyl-anion complexes in the gas phase using ion-trap mass spectrometry (IT-MS). Several recent reports have demonstrated that intrinsic metal and metal complex chemistry can be investigated by the (controlled) addition of reagent gas to an ion trap [12][13][14][15][16][17][18][19][20][21][22], or by way of the presence of H 2 O and other small molecule contaminants within the He bath gas used to collisionally cool ions and improve trapping efficiency [23][24][25]. The reactions of uranium ions in the gas phase have been the subject of several earlier investigations.…”
mentioning
confidence: 99%